Survey Tingkat Penggunaan Single Sign On pada 500 Situs Peringkat Teratas Alexa.com - Suhartanta, I Wayan Manik; Sastra, Nyoman Putra (Majalah Ilmiah Teknologi Elektro, 2017)
Advances in Internet technology has provided a new market for the growth of the service provider. New sites appear in large numbers every year. This gives a new problem for users of the service. Users are forced to memorize many username and password to access the service. Overcoming it is a new emerging technology, the technology called Single Sign On (SSO). SSO offers simple authentication process for users to access many services sites. But the level of confidence of users and service providers, in the use of SSO technology have not been investigated. In this research shows that the rate of utilizing the SSO technology of the top 500 sites on alexa.com by 31% (155 websites). And the level of utilization of the SSO more than one provider, by 41%. In studies it appears that the most used SSO services provider is google followed by facebook and twitter. (turnitin check 9%) Keyword— Single Sign On (SSO), Computer Security, Authentication   DOI: 10.24843/MITE.1601.07
Keywords: Single Sign On (SSO), Computer Security, Authentication